Uma proposta para o ensino de geometria analítica através da resolução de problemas e do uso do geogebra - Cardoso, Carlos Eduardo (Universidade Federal de São Carlos, 2016)
The concern with the basic teaching of mathematics have grown over the past years. The results presented in external evaluations and even the performance in the classroom have worried experts in education and our entire society. This study was carried out in order to seek an improvement in education and show the real sense of the mathematical concepts. We sought to develop and propose a didactic sequence that promotes students’ understanding of the key concepts of analytic geometry covered in high school showing by solving problems, geometric idea behind each algebraic development conducted over the activities proposals. It also sought to combine the technology with the help of Geoge- bra, the activities that were conventionally worked in the classroom, providing an extension of the conceptual view by the students. The didactic sequence and the results presented below were designed and rigorously applied in the classroom as well as having always been planned with the goal of transforming the student as the protagonist of ones own knowledge. So it was presented a proposal based on the Didactic Engineering which combines the geometric vision with the algebraic development not letting aside that mathematical concepts are fundamental to the intellectual development of our students.
Keywords: Geometria analítica; Geogebra; Resolução de problemas; Engenharia didática; Analytic geometry; Didactic engineering; Troubleshooting; CIENCIAS EXATAS E DA TERRA::MATEMATICA